2023
DOI: 10.7759/cureus.43826
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Foot Drop After Leg Traction on Fracture Table for Mid-Shaft Femur Fracture Nailing: A Rare Case Report

Jehad A Alzahrani,
Ahmed A Alabdali,
Mohammed O Albariqi

Abstract: Femoral shaft fracture, one of the most common orthopaedic injuries, is usually treated with intramedullary nailing. During the operative procedure patients are placed on a traction table. Traction tables facilitate the procedure but are associated with some risk. Here we are sharing a case of a 35-year-old male healthy young patient who sustained a foot drop post nailing of femoral shaft fracture on a traction table. This patient has had some recovery in six weeks but is still not fully recovered. We think tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…It could be due to the entrapment of the nerve as a result of the fracture, or due to hematoma formation post-operatively [ 10 , 11 ]. However, Alzahrani et al reported ipsilateral foot drop post femur IMN related to the traction table similar to our case which made us consider mispositioning of the fracture table as a reasonable cause [ 12 ]. Finally, these complications can be addressed by decreasing procedure time, enhancing the position of the patient, and providing sufficient padding of the perineal post.…”
Section: Discussionsupporting
confidence: 76%
“…It could be due to the entrapment of the nerve as a result of the fracture, or due to hematoma formation post-operatively [ 10 , 11 ]. However, Alzahrani et al reported ipsilateral foot drop post femur IMN related to the traction table similar to our case which made us consider mispositioning of the fracture table as a reasonable cause [ 12 ]. Finally, these complications can be addressed by decreasing procedure time, enhancing the position of the patient, and providing sufficient padding of the perineal post.…”
Section: Discussionsupporting
confidence: 76%